The dialectic of the familiar and the unfamiliar in Islamic photography (Al-Academy, 2023)
This research is concerned with the study of (the dialectic of the familiar and the unfamiliar in Islamic photography), and it consists of four chapters.If you dealt with the problem of the research subject (the dialectic of the familiar and the unfamiliar in Islamic photography, as it appeared realistic, familiar forms and strange and strange unfamiliar forms represented in many of the main schools of Islamic photography that emerged in Iraq and Persia and then the Ottomans and the However, Islamic painting still retains those previously witnessed and unseen images, which pose themselves forcibly in the form of many questions that must be faced and studied by investigation, observation, extrapolation and conclusion through scientific research. The problem of research also lies in asking whether the Muslim artist intended to He puts those familiar forms of man with previously unfamiliar forms of the eye. Either he represents them through reality and myth together, or the fictional narration of the heavenly books, or by combining the two sides of the equation for the familiar and the unfamiliar in establishing its rules and technical principles for such a complex phenomenon Which is: revealing the dialectic of the familiar and the unfamiliar in Islamic photography. The first chapter included the objective, temporal and spatial boundaries and the definition of the most important terminology mentioned in the research. The second chapter was devoted to the theoretical framework, which was divided into two sections. The first concerned the familiar and the unfamiliar in Islamic philosophical thought. The second topic concerned the epistemological and aesthetic approaches to the art of Islamic painting. To reach the third chapter represented by the research procedures: including the research community and its large sample (3) of the artistic depictions of Islamic photography. The fourth chapter was devoted to the results of the research, conclusions, recommendations, and proposals. Among the most prominent results that the researcher reached: the emergence of familiar and realistic images of man and existence together with non-spiritual images Familiar ones, such as people with sacredness, such as images of messengers, prophets, the House, angels, people of knowledge and authority distributed between the world of theology and the world of humanity, where the unseen or unfamiliar spiritual side prevailed in this dialectic that connects the upper world with the lower world or connects everything that is realistic and lived with what is. Unfamiliar and hypothetical by Muslim artist and whoThis is what the research came up with, as well as the conclusions, research recommendations, suggestions, and sources.